PENCEGAHAN KEKERASAN TERHADAP ANAK SEBAGAI MODAL PEMENUHAN HAK DASAR PENDIDIKAN - Muhammad Mahbub (LPPM IAI QOMARUDDIN GRESIK, 2020)
In the law of the child act number 23 of 2002 concerning to the child’s protection explains that a child is any person under the age of 18 including any unborn child. Meanwhile, the child right is all the basic needs of the child that must be respected, protected, and fulfilled so that the welfare and life of the child is protected by the law. In the Convention of on the Rights of the Child (CRC), child's right is grouped into: the right to live, the right to grow and develop, the right to get protection, and to participate. On the other hand, education is the manifestation and implementation of the child's right, supervision of the learning process, scheduling the learning time, providing the child's learning need and solving the child's learning difficulties are part of the obligations that parents must fulfill for the basic rights of child's education. In fulfilling the parents' obligations to the child's learning process is not only measured by how much financial given, but is also measured by the attention and assistance on the child’s learning difficulties. In accordance with the topic, this research aims to: (1) providing knowledge of the basic rights of child, (2) providing an understanding about what so- called violence against child, (3) providing skills on how to prevent child abuse, and (4) the fulfillment of parents' obligations towards child’s right as a form of prevention of violence against children. This study employs the theory of change with a quantitative-exploratory approach, the terms of exploratory has positioned the previous findings as a basis ideas and problem solving in this research, thus giving ideas and solutions dealing with the problem that “the fulfillment of child's right is an integral part of preventing violence against children.” It will be very beneficial for parents and teachers as the partners of children in enhancing their education, thus creating an atmosphere conducive academic to child's learning. Keywords; violence, basic rights, education